Didactic use of simulation programmes and their application in teaching Earth Sciences - Pardo Santano, Pablo; Roura Redondo, Margarita (Pulso. Revista de educación, 2001)
In general, information technologies and simulation programmes have the potential to be highly effective teaching tools with diverse applications. In Earth Sciences, they are particularly valuable for overcoming traditional challenges associated with studying this subject. Specifically, these challenges are often linked to spatio-temporal complexities and the difficulty, or impossibility, of replicating certain natural processes.